A case of large developing odontoma, so-called ameloblastic fibro-odontoma, of the mandible. Issue 5 (September 2019) - Watanabe, Hideki; Osano, Hitoshi; Igarashi, Hisao; Dohi, Akihiro; Mori, Yoshiyuki
Abstract: Large developing odontoma is a rare odontogenic tumor showing proliferation of both odontogenic epithelium and ectomesenchyme, with enamel and dentin formation. A case of large developing odontoma affecting the lower molar region to the mandibular ramus of a 14-year-old girl is reported. Panoramic and computed tomography images showed a clearly demarcated, multilocular radiolucency extending from the left lower molar region to the mandibular ramus, containing a tooth-like radiopacity. With the patient under general anesthesia, the mass was removed. The histopathological diagnosis was developing odontoma. There was no sign of recurrence at 1 year after tumor removal.